2016
DOI: 10.1016/j.amepre.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Online Patient–Provider E-cigarette Consultations

Abstract: Introduction E-cigarettes are popular and unregulated. Patient–provider communications concerning e-cigarettes were characterized to identify patient concerns, provider advice and attitudes, and research needs. Methods An observational study of online patient–provider communications was conducted January 2011–June 2015 from a network providing free medical advice, and analyzed July 2014–May 2016. Patient and provider themes, and provider attitudes toward e-cigarettes (positive, negative, or neutral) were cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
0
18
0
11
Order By: Relevance
“…Incidence rates of patients' ENDS use based on clinician documentation in the EHR have increased dramatically in recent years, likely reflecting both surges in patient uptake of ENDS and greater patient-provider discussions about ENDS (Young-Wolff et al, 2017;Brown-Johnson et al, 2016). As expected, current smokers-and former smokers, to a lesser extent-had higher incidence rates of ENDS-use documentation each year than never-smokers.…”
Section: Discussionmentioning
confidence: 59%
“…Incidence rates of patients' ENDS use based on clinician documentation in the EHR have increased dramatically in recent years, likely reflecting both surges in patient uptake of ENDS and greater patient-provider discussions about ENDS (Young-Wolff et al, 2017;Brown-Johnson et al, 2016). As expected, current smokers-and former smokers, to a lesser extent-had higher incidence rates of ENDS-use documentation each year than never-smokers.…”
Section: Discussionmentioning
confidence: 59%
“…Some research has shown that patient's questions about NVPs do not always directly relate to smoking cessation specifically, and can more generally be about the harm and safety of NVPs (including side effects, nicotine health risks and addiction issues). For example, one online study of licensed HPs from various disciplines found that half of providers reported having discussed vaping as a harm reduction option, while 26% discussed vaping as a quit aid . Our study suggests that HPs who are offering direct smoking cessation advice to their patients (and perhaps more regularly assess smoking status and cessation) may be more willing to recommend NVPs as a quit smoking aid.…”
Section: Discussionmentioning
confidence: 76%
“…Our findings showed that, overall, fewer than 10% of smokers reported having a discussion about NVPs with an HP in the last year. Moreover, a number of studies have shown that HPs are divided about recommending NVPs for smoking cessation . The results herein have shown that HPs rarely recommended NVPs to smokers (only 2% of smokers were encouraged to use an NVP, which was approximately a third among those who had a conversation about the topic).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Tracking ENDS use through routine documentation within healthcare visits could yield important surveillance data for studying population-level harm and harm reduction effects. National guidelines strongly recommend that tobacco screening in healthcare settings be expanded to include ENDS questions as part of standard health examinations (American Heart Association, 2016; The American Academy of Pediatrics Issues Sweeping Recommendations on Tobacco and E-Cigarettes, 2015), and healthcare providers are increasingly discussing ENDS use with patients (Nickels et al, 2016; Steinberg et al, 2015; Brown-Johnson et al, 2016). Routine clinician screening and documentation of ENDS use in the EHR could be linked to other healthcare data for retrospective and prospective analyses essential to assessing ENDS’ safety and harm reduction effectiveness.…”
Section: Introductionmentioning
confidence: 99%